2021
DOI: 10.1136/bmjdrc-2020-002070
|View full text |Cite
|
Sign up to set email alerts
|

Trigger finger is associated with risk of incident cardiovascular disease in individuals with type 2 diabetes: a retrospective cohort study

Abstract: IntroductionTrigger finger is one of the complications affecting the upper extremity in patients with diabetes. Diabetes is also a well-known risk factor that predisposes individuals to cardiovascular diseases (CVDs). This retrospective cohort study aimed to establish the association between trigger finger and the patients with incident CVD with type 2 diabetes.Materials and methodsTrigger finger was diagnosed by palpating a thickened tendon during flexion or on the manifestation of a locking phenomenon during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…[ 17 ] One of the previous research papers indicated that the trigger finger is related to the incidence of cardiovascular disease (CVD) in patients with type 2 diabetes. [ 18 ] Diagnosis of trigger finger is relatively easy and noninvasive.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] One of the previous research papers indicated that the trigger finger is related to the incidence of cardiovascular disease (CVD) in patients with type 2 diabetes. [ 18 ] Diagnosis of trigger finger is relatively easy and noninvasive.…”
Section: Discussionmentioning
confidence: 99%
“…In the results section, our findings suggest that the presence of hypertension in patients, along with trigger finger, escalate the pain level. Previous studies found that hypertension can lead to inflammation and the deposition of collagen in the tendons, which may lead to pain [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genes, including KLHL1 and POLE2, could be a possible reason for stenosing tenosynovitis [5]. Diabetic individuals have a higher rate of stenosing tenosynovitis incidence, especially among type 2 diabetes patients [6][7][8][9]. People with diabetes have stenosing tenosynovitis between 4 and 29 percent and are thought to account for around one-third of all stenosing tenosynovitis cases [6].…”
Section: Groups/activities At Riskmentioning
confidence: 99%
“…On rare occasions, a perceptible lump could be experienced moving along the segment with finger flexion and extension [15]. The most important clinical finding is a brief obstruction of the digit during flexion, followed by painful snapping during extension [16][17]. Localized soreness is present around the neck of the metacarpal, and when the digits are moved [15].…”
Section: Symptomsmentioning
confidence: 99%
See 1 more Smart Citation